Música e internacionalismo no Noticiero ICAIC Latinoamericano - Camila Arêas; Glauber Lacerda; Ivette Céspedes (Caravelle)
Music serves as a narrative guide in the Cuban newsreel Noticiero ICAIC Latinoamericano (1960-1990). For three decades, the programme publicized the left-wing struggles of the Third World, propagating an ideal of solidarity between peoples oppressed by imperialism. This study examines the strategies used to musicalise images within the Cuban cultural project to build an internationalist and mainly Latin American identity for the Cuban audience.